Finite element analysis of shape accuracy of billet cold-forged with stepwise ram motion - Ryo MATSUMOTO (The Japan Society of Mechanical Engineers, 2019)
Influence of stepwise ram motion, one of practical ram motion controls of servo press, on shape and dimensional accuracies of forged billet was investigated in cold cup forging process by the finite element analysis. In the process with stepwise ram motion, the billet inserted in the container was forged by the punch with upper ram of press, and the punch was operated with repetition of advance and pause modes. Following four stages were analyzed; (i) forging, (ii) removal of the punch from the forged billet, (iii) ejection of the forged billet from the container by the knockout punch and (iv) air cooling of the forged billet. In the analysis, the shape and dimensional changes of the inner wall of the billet during the four stages were investigated with several stepwise ram motions under the same forging duration. It is found that repetition of the punch advance with short stroke reduces heterogeneity of the temperature and stress distributions, so that the shape and dimensional accuracies of the inner wall of the forged billet were improved. The results of the finite element analysis were confirmed to be qualitatively agreed with the results of forging experiment on a link-type servo press.